Using ICT during preservice teachers’ autonomous study - Sarreira, Pedro (2020)
In this article we assess the implementation of four learning objects directed to different basic astronomy subjects. A questionnaire aiming at assessing preservice teachers’ perception on the use of the learning objects in self-study was applied after an initial exploration of the learning objects in the classroom. This took place during a four-week teaching and learning of astronomy in a preservice teacher course. Most of respondents report positive impact both at emotional as well as at cognitive level. Some differences are reported in relations to the structure of the learning objects, which we discuss.